Accuracy of paratuberculosis diagnostic tests in small ruminants: protocol for a systematic review and meta-analysis. (19th June 2019) - Buczinski, S.; Arsenault, J.; Kostoulas, P.; Corbière, F.; Fecteau, G.; Dendukuri, N.
Abstract: Paratuberculosis is a worldwide infectious disease caused by Mycobacterium avium ssp. paratuberculosis (MAP). Various ruminant species can be affected by the disease, and the diagnosis of the disease is challenging in the absence of a gold standard test. The aim of this systematic review protocol is to determine the accuracy of the direct and indirect diagnostic tests for MAP infection with a special focus on sheep and goats.